Komunikasi Lingkungan dalam Budaya Masyarakat (Analisis Model Pesan Two Way Asymmetrical pada Lembaga Adat) - Dhanurseto Hadiprashada; Dwi Aji Budiman (Jurnal Komunikasi, 2019)
The lack of documentation related to the potential of cultural values on the island of Sumatra provides obstacles for the community. This case especially happen in the pattern of delivering messages in the communication process. This condition provides a lot of intepretation to understanding about regulations related of cultural values. Therefor these obstacles can occur at various levels. It can be seen in the regulation of the government system, at the district and provincial level, and  traditional institutions in each province. This study aims to examine the related message of two way asymmetrical message model in creating synergy in environmental communication patterns in the cultural wisdom of the people in Bengkulu province. This research was conducted using a case study approach in qualitative research. Collecting data procedure used in this study was purposive sampling, which is taking all information in research within accordance certain criteria, using purposive sampling. In-depth interviews were conducted with informant in the goverment institution we call it Badan Musyawarah Adat (BMA) and independen traditional institution, Aliansi Masyarakat Adat Nusantara (AMAN) in the Bengkulu region, which is a community organization focused on issues of customs and culture.The results show that the two way asymmetrical message model that occurs in one process, can actually create a pattern of relationships between the environment, and communication. This message model directly sees the environment as an important object. The environment becomes a model for the formation of messages that are informative for the community in carrying out activities related to the information they are receiving. The process of studying messages, the cultural values of society can actually revitalize the culture itself in the process of forming the message that has been conveyed. This is what causes the symbolic meaning in the wisdom of communication in the community environment.memberikan hambatan tersendiri bagi masyarakat. Khususnya dalam pola penyampaian pesan dalam proses komunikasi. Kondisi ini memberikan banyak ruang dalam pemahaman atas regulasi terkait nilai budaya tersebut. Hambatan ini dapat terjadi dalam berbagai tingkatan. Seperti dalam regulasi sistem pemerintahan, di tingkat kabupaten, provinsi dan pada lembaga-lembaga adat yang ada di setiap provinsi. Penelitian ini bertujuan untuk melakukan kajian terkait model pesan dalam menciptakan sinergisitas pola komunikasi lingkungan dalam kearifan budaya masyarakat di Provinsi Bengkulu. Penelitian ini dilakukan dengan menggunakan pendekatan studi kasus dalam penelitian kualitatif. Prosedur pengambilan data yang digunakan dalam penelitian ini adalah purposive sampling, yaitu mengambil semua informasi yang sesuai dengan kriteria tertentu, dengan menggunakan pengambilan sampel bertujuan (purposive sampling). Wawancara mendalam dilakukan kepada informan yaitu, Badan Musyawarah Adat, (BMA) yang menangani permasalahan adat istiadat di Provinsi Bengkulu dan Aliansi Masyarakat Adat Nusantara (AMAN) wilayah Bengkulu yang merupakan organisasi masyarakat yang fokus dalam masalah adat dan budaya. Hasil penelitian menunjukkan bahwa model pesan two way asymmetrical yang terjadi dalam satu proses, ternyata dapat menciptakan pola hubungan antara lingkungan, dan komunikasi.  Model pesan ini secara langsung melihat lingkungan menjadi sebuah objek yang penting. Lingkungan menjadi sebuah model pembentukan pesan yang bersifat informatif bagi masyarakat dalam menjalankan aktivitas terkait informasi yang sedang mereka terima. Proses pada telaah pesan, nilai- nilai budaya masyarakat ternyata dapat merevitalisasikan budaya itu sendiri dalam proses pembentukan pesan yang telah tersampaikan. Hal ini yang menyebabkan adanya pemaknaan simbolik dalam kearifan komunikasi dalam lingkungan masyarakat.